Manajemen Inovasi Pembelajaran Pendidikan Agama Islam Berbasis Digital di Era Society 5.0 - Nur Khozin; Edi Ahyani; Ahl Allah; Andi Rahmat Abidin (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the management of digital-based Islamic Religious Education (PAI) learning innovations in the Society 5.0 era. The approach used is qualitative with literature study methods and descriptive analysis. The data sources in this study come from scientific journals, books, research articles, and documents related to digital learning and Islamic education that are relevant to the research theme. Data collection techniques were carried out through documentation studies and literature review of various scientific references that support the study. The data analysis technique uses qualitative descriptive analysis with stages of data reduction, data presentation, and conclusion drawn. The results of the study show that PAI learning innovation management includes planning, implementation, and evaluation based on digital technology such as e-learning, interactive media, and online learning platforms. This innovation is able to increase the effectiveness of learning, student involvement, and internalization of Islamic values. However, there are challenges in the form of limited digital competencies of teachers and infrastructure. Therefore, an adaptive and sustainable management strategy is needed to support the optimal implementation of digital-based PAI learning in the Society 5.0 era.